Color-coded molecular beacons for multiplex PCR screening assays - Marras, Salvatore A. E. (PLoS One, 2019)
The number of different fluorescent colors that can be distinguished in a PCR screening assay restricts the number of different targets that can be detected. If only six colors can be distinguished, and the probe for each target is labeled with a unique color, then only six different targets can be identified. Yet, it is often desirable to identify more targets. For instance, the rapid identification of which bacterial species (if any) is present in a patient’s normally sterile blood sample, out of a long list of species, would enable appropriate actions to be taken to prevent sepsis. We realized that the number of different targets that can be identified in a screening assay can be increased significantly by utilizing a unique combination of two colors for the identification of each target species. We prepared a demonstration assay in which 15 different molecular beacon probe pairs were present, each pair specific for the same identifying sequence in the 16S ribosomal RNA gene of a different bacterial species, and each pair labeled with a unique combination of two fluorophores out of the six differently colored fluorophores that our PCR instrument could distinguish. In a set of PCR assays, each containing all 30 color-coded molecular beacons, and each containing DNA from a different bacterial species, the only two colors that arose in each real-time assay identified the species-specific target sequence that was present. Due to the intrinsic low background of molecular beacon probes, these reactions were specific and extremely sensitive, and the threshold cycle reflected the abundance of the target sequence present in each sample.